Do you remember your first drama lesson? Critical Incident methodologies for future practice - Pascoe, Robin (Education & Theatre, 2023)
Reading accounts of the summer camps for drama education organised by the Hellenic Theatre/Drama & Education Network reminded me of an early inciting incident in my own drama teaching: working as an intern on a summer camp for children from remote and regional Western Australia while I was a student at university. In reflecting on the experience, I thought it important to do more than indulge in an exercise in nostalgia. In my current work as a semi-retired teacher at Murdoch University, I work with students on Critical Incident methodology. This article merges reflection and reflexivity as a process of personal professional growth.